Temporal and spatial variability of the landfast ice cover in the Bothnian Bay - Saloranta, Siiri Kirsikka (Helsingin yliopisto, 2025)
Landfast ice, the relatively stable ice cover attached to coasts and islands, has a major influence on the surrounding environment, as it protects the coast from erosion, dampens the interaction between the sea and the atmosphere, and affects coastal and marine infrastructure, among other things. The ice conditions in the Baltic Sea are largely depended on atmospheric patterns, making interannual variation notable. Locally, ice conditions are also affected by for example bathymetry, temperature and winds. The ongoing climate change is projected to cause diminishing in the extent, duration and thickness of sea ice in the Baltic Sea. Landfast ice has not, however, received as much attention as drift ice in scientific studies. This work examines the temporal and spatial variation of the landfast ice cover in the Bothnian Bay during winters 2007-2021. Over 2000 ice charts describing the daily ice conditions in the Baltic Sea were used. Average and maximum landfast ice extent and duration were defined, alongside with the first and last date of the occurrence of landfast ice, and the date when the maximum extent of landfast ice occurred each winter. The relationships between landfast ice presence and environmental data were studied with a general additive model. For the temporal analysis, the results indicated a decreasing trend in the maximum and average landfast ice extent, but the trends were not significant. For the spatial analysis, bathymetry was the most important variable affecting landfast ice presence. There are still a lot of possible future research questions for landfast ice. In the face of the ongoing climate change, when the changing landfast ice cover might increase coastal and seafloor erosion, infrastructure damage and changes in local ecosystems and climate patterns, further studies are urgently needed. Kiintojää on suhteellisen tasainen jääpeite, joka on kiinnittynyt rannikoihin ja saariin, ja joka vaikuttaa voimakkaasti ympäristöönsä, esimerkiksi suojaten rannikkoa eroosiolta, vaimentaen meren ...